Aspek logis dalam pernyataan-pernyataan politik - Hayon, Y. P. (UI Scholars Hub, 2005)
Each political formula in the form of a statement (argument) always has a direct interconnected political purpose relative to an important group. This importance factor becomes basic consideration in the formulation of a political statement in such a manner that it can influence public emotion and feeling producing desired agreement and response from the public. Because a wide segment of society becomes special target, with their different levels of education and understanding, the logical aspects are considered unimportant and subject to elimination. The important thing is how to encourage public emotion and encourage the public to response according to what the politicians want. That is why many political statements are irrational (argumentum ad populum), having no consistency between the premise and the conclusion. Many political statements commit the fallacy of composition, shifting the distributive understanding to collective understanding. This article examines the types of fallacies in political staements by presenting actual cases as illustrations.